Malaysia: Financial Liberalization in the Banking Industry - Loke, Lee Lian (2011)
In this globalised era, financial liberalization is indeed crucial to support the functioning of the worldwide economies. As a developing country which is striving to achieve the developed nation status by year 2020, Malaysia too has liberalized the financial industry, particularly the banking sector. However, the liberalization strategy was more conservative and gradual, focusing primarily on building strong fundamentals in the industry before further liberalizing the sector. The Governor of Bank Negara Malaysia has stressed that financial liberalization must result in a win-win situation for the domestic banking sector and the foreign players. Advocates and opposing parties of financial liberalization had strongly debated on this issue, with both having equally strong points to support their arguments. Thus, it is clear that although financial liberalization is the way forward for the world economies, there is no firm decision on how the liberalization strategy should be. Rather financial liberalization should be carried out based on the circumstances of the various countries. In the 1990s, there were numerous controls imposed on the domestic banking institutions or more commonly termed as financial repression. Some of the controls had been beneficial such as enabling the development of the Malaysian banks which are now strong enough to expand their presence in the international arena. Nevertheless,there are other controls which are not so favorable, as should only be used under certain conditions i.e. capital control. As Malaysia is moving for further financial liberalization, there are several challenges for the country to ensure a successful liberalization. The banking industry also needs to have strong governance framework, robust risk management system as well as enhanced prudential regulatory and supervisory framework to ensure a resilient financial industry. Central banks across the globe have enhanced their collaboration to monitor any arising risks.